A new algorithm for reconstructing tree height growth with stem analysis data. Issue 10 (5th July 2021) - Salas‐Eljatib, Christian
Abstract: Stem analysis allows us to obtain an abundant amount of information on tree growth. A couple of algorithms exist to utilize section height and growth ring data for reconstructing height and age time‐series information. I evaluated two alternatives, a well‐known and a newly proposed algorithm using stem analysis data of four species, including deciduous and evergreen broadleaves and a conifer. I reconstructed height–age pairs by both algorithms. I fit height growth equations in a mixed‐effects model framework for each species, using the generated data with the respective algorithm. Comparisons considered confidence intervals of the estimated parameters, as well as regression‐based equivalence tests. Results showed that the fitted growth models obtained from both stem analysis algorithms were statistically equivalent. However, the proposed algorithm is simpler and thus provides a useful alternative to current methods. Based on the findings, I recommend using this new stem analysis algorithm to reconstruct tree height growth with stem analysis data. Resumen: El análisis fustal permite obtener abundante información del crecimiento de los árboles. Existen una cantidad importante de algoritmos que utilizando los datos de los anillos de crecimiento en cada sección permiten reconstruir las series de tiempo altura‐edad. Evalué dos alternativas, un algoritmo muy conocido y otro nuevo propuesto usando datos de análisis fustal provenientes de cuatro especies, incluyendo latifoliadas deciduas y siempreverdes y una conífera. Reconstruí los pares de datos altura‐edad con ambos algoritmos. Luego, a partir de los datos generados por cada algoritmo, ajuste una ecuación de crecimiento en altura mediante modelos de efectos mixtos para cada especie. Finalmente, compare los intervalos confidenciales de los parámetros estimados de los modelos de crecimiento, así como también mediante pruebas de equivalencia. Los resultados indicaron que los modelos de crecimiento obtenidos a partir de los datos generados por ambos algoritmos son estadísticamente equivalentes. Sin embargo, el algoritmo propuesto es más simple y por lo tanto ofrece una alternativa muy útil a los métodos actuales. Basado en esta investigación, recomiendo usar este nuevo algoritmo para reconstruir el crecimiento en altura a partir de datos de análisis fustal.